A Review on Peanut Shell Powder Reinforced Polymer Composites. Issue 4 (4th March 2019) - Zaaba, Nor Fasihah; Ismail, Hanafi
ABSTRACT: Recently, the critical discussion about the innovation of superior properties of engineering products that produced from natural resources has led to the renewed interest worldwide, concerning renewable and environmental issues. Rigorous study has been conducted on the natural fillers by both academicians and industrial researchers. Amongst the various sorts of natural resources, peanut shell powder has been considerably utilized over the past few years. Therefore, this study raises an overview with a specific focus on the improvements made in the scope of peanut shell powder reinforced polymer composites in various type of polymer matrices (i.e. thermoplastic, thermoset and natural rubber). GRAPHICAL ABSTRACT: